2007
DOI: 10.1002/art.22690
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory rheumatic disease and smoking are predictors of aortic inflammation: A controlled study of biopsy specimens obtained at coronary artery surgery

Abstract: Objective. Several inflammatory rheumatic diseases are associated with accelerated atherosclerosis. Atherosclerosis may result from systemic and/or local vascular inflammation. The aim of this study was to evaluate the occurrence of chronic inflammatory infiltrates in the aortas of patients with and those without inflammatory rheumatic disease who had undergone coronary artery bypass graft (CABG) surgery, and to assess the relationship between the infiltrates and other factors thought to play a role in atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…The biopsy specimens were fixed in formalin, embedded in paraffin, and cut in 3‐μm–thick sections. Some findings regarding the aortic adventitia and internal thoracic artery used in this study have been reported previously 6, 9.…”
Section: Methodssupporting
confidence: 60%
“…The biopsy specimens were fixed in formalin, embedded in paraffin, and cut in 3‐μm–thick sections. Some findings regarding the aortic adventitia and internal thoracic artery used in this study have been reported previously 6, 9.…”
Section: Methodssupporting
confidence: 60%
“…Giant cells were present in the aorta only, in a single patient with psoriatic arthritis. 3 The occurrence of MCIs in the SV was not statistically significantly associated with age, gender, presence of vascular calcification, smoking, body mass index, diabetes mellitus, hypertension, hypercholesterolemia, family history of coronary artery disease, acute coronary syndrome, duration of coronary artery disease, C-reactive protein, erythrocyte sedimentation rate, current use of oral glucocorticosteroids, disease-modifying drugs, nonsteroidal anti-inflammatory drugs, or statins. The occurrence of MCIs in the IMA was too low to look for such relationships.…”
Section: Biopsy Findingsmentioning
confidence: 82%
“…Most of the aortic findings were published previously. 3 Preoperative physical findings, medical history, treatment, and previous and current smoking of cigarettes (yes/no) were recorded, and blood tests were performed. The surgeons noted gross signs of pathology in the SV and IMA vessel walls and the quality of the venous conduit (good, medium, or poor).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations